“I feel like it should be but I know it’s really not”: exploring physical fitness priorities at the correctional training program in Canadian federal corrections - Zachary Towns; Rosemary Ricciardelli; Dale C. Spencer (International Journal of Qualitative Studies on Health & Well-Being)
The correctional training program (CTP), composed of three stages, includes a 14 week in-person component that Correctional Officer Recruits (CORs) must complete prior to their employment as a federal Correctional Officer (CO) for Correctional Service Canada (CSC). The CTP prepares recruits for a plethora of CO responsibilities, some dependent on physical fitness, such as responding to codes being called, physical altercations, or violent situations. Unlike other public safety positions (e.g. policing, border services, or coast guard) CSC does not require occupational fitness testing. In the current article, we use data from a multiyear longitudinal study of federal COs from across Canada to unpack how CORs manage physical fitness expectations at CTP; CSCs’ expectations of COR physical fitness; and outline what types of physical fitness (e.g. weightlifting, cardiovascular, self-defence) are taught, thus valued most, during CTP. We situate the voices of CORs regarding physical fitness within the broader “body” literature and discuss policy recommendations tied to physical fitness, specifically COs’ interest in reinstating pre-employment physical fitness screening.